Application of nanostructured emitters for high efficiency lighting - Searle, A (2014)
This is the first study comparing morphologies of CNT films on Kanthal wire, with their field emission properties, and as such offers ways to design better cylindrical emitter devices. A low turn-on field was achieved (0.35 V/µm), the field emission results have been explained using a simple model, and a fluorescent lamp was fabricated. Whilst previous work has been done on the link between “as grown” CNT films and their respective field emission properties on flat substrates, very little work has been done on linking morphology to emission performance on wire substrates, where the morphology can be very different. Microscopic structures such as towers, ridges and clumps consisting of many aligned or entangled CNTs were grown using an aerosol chemical vapour deposition (a-CVD) technique. Hydrogen added to the carrier gas resulted in a decrease in defect density in the growth of undoped CNTs, and an increase in defect density in the growth of nitrogen doped CNTs (N-CNTs) and boron doped CNTs (BCNTs). In-situ transmission electron microscopy (TEM) studies show that damage to CNT tips results in a significantly higher turn-on field compared to undamaged tips. This can be recovered by making the CNT emit current for several minutes which makes the tip recrystallize due to heat caused by the Nottingham effect. The field emission properties of the “as grown” CNT films are dominated by protruding CNTs found at the edges of ridge and tower microscopic structures. The field emission properties are also related to the dimensions of these structures with the longest ridges (hence those with the longest protruding CNTs) resulting in the lowest turn-on electric field. The ridge and tower structures act to accommodate protruding CNTs at their edges and their physical dimensions (mainly width) act to separate these emitters so that screening is minimised. This work shows that efficient emitters can be fabricated effectively from simple a-CVD techniques and microscopic structures act to improve, not degrade, field emission properties.